On Subclass of 𝑘-Uniformly Convex Functions of Complex Order Involving Multiplier Transformations - Waggas Galib Atshan; Ali Hamza Abada (Abstract and Applied Analysis)
We introduce a subclass of 𝑘-uniformly convex functions of order 𝛼 with negative coefficients by using the multiplier transformations in the open unit disk 𝑈={𝑧∈ℂ∶|𝑧|<1}. We obtain coefficient estimates, radii of convexity and close-to-convexity, extreme points, and integral means inequalities for the function 𝑓 that belongs to the class 𝒩ℓ𝑚(𝛼,𝛽,𝑘,𝜐).